Cost Analysis Of Low Rise Buildings Subjected To Seismic And Non Seismic Action - Teo, Chia Chia (Universiti Sains Malaysia, 2019)
Earthquake is a natural phenomenon that has a greater impact towards the economy and community. Malaysia is located on low to moderate seismic zone, thus almost structures were designed according to BS8110 which does not consider the seismic action. In this study, two existing low rise buildings, namely Pra Sekolah and JKR Cawangan Mekanikal were redesigned for earthquake resistance with the aid of ETABS 2016 commercial software. The aim is to identify the increase in the material construction cost due to the seismic loading. Two low rise building models were generated and redesigned in considering of the seismic loading. The seismic loading was applied to the structure by using modal response spectrum method. The parameter of the seismic load include soil condition, behaviour factor, ductility classes and peak ground acceleration were determined according to Eurocode 8. The material quantities such as concrete volume and weight of reinforcement were determined by taking off process. The results showed that the concrete volume and steel reinforcement increased due to seismic loading. Besides, the material costs increased by 28.35% and 26.19% for Pra Sekolah and JKR Cawangan Mekanikal, respectively. In this study, two different types of soil condition (Type C and D) were used to evaluate the overall material quantity. The two different soil condition showed insignificant change in the material quantities.